Man-Nature Relationship in L P Devkota’s Poems: An Ecological Study - Dhungel, Nabaraj (Literary Studies, 2020)
Man-nature relationship is one of the central themes of great poet Laxmi Prasad Devkota. This relationship is both analogous and Antithetical. Nature is source of life, knowledge and pleasure foe human beings. But at the same time it is cruel and angry giving pain and suffering to human beings. Similarly, man both loves and exploits the nature. On the one hand, they worship nature as god but on the other hand, they make it the source of earning deteriorating it. Instead of enjoying its beauty and positively using nature, human beings try to get maximum profit from nature irrationally utilizing it which causes adverse effects in the ecosystem and the whole universe. Many of his poems focus on mundane elements of the human and the natural world.